1997
DOI: 10.1063/1.474711
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of the methoxy radical in small clusters

Abstract: In this work we analyze clusters between the methoxy radical (CH3O, an open-shell molecule) and the nonpolar solvents Ar, N2, CH4, and CF4. CH3O is formed through the photolysis of CH3OH vapor in a supersonic expansion of CH3OH and a solvent gas (Ar, N2, CH4, CF4) seeded in a carrier gas of He. The radical and solvent molecules are cooled to ∼15–20 K and form clusters. These clusters are probed using laser induced fluorescence (LIF) of the CH3O radical. An extensive set of calculations, including ab initio and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…16 Usually, two different theoretical approaches have been adopted to study the solvation of radical species. The first one is based on "microsolvation" in small clusters, 9,[17][18][19][20][21][22] and it has been applied to a variety of free radical systems.…”
Section: Introductionmentioning
confidence: 99%
“…16 Usually, two different theoretical approaches have been adopted to study the solvation of radical species. The first one is based on "microsolvation" in small clusters, 9,[17][18][19][20][21][22] and it has been applied to a variety of free radical systems.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In the fluorescence excitation experiments, a general valve pulsed nozzle is used to generate an adiabatic expansion of the appropriate mixture of molecular precursor for Xcpd ͑Ͻ1% of the total pressure͒, the solvent gas ͑0.1%-10% of the total pressure͒, and 50-400 psi He expansion gas. The stainless steel vacuum chamber into which the mixture is expanded remains at ϳ10 Ϫ4 Torr during the FE experiment.…”
Section: A Experimentalmentioning
confidence: 99%
“…Nonetheless, relatively few studies involving radicals and clusters can be found in the literature, due in part to the significantly increased difficulties encountered in generating, isolating, cooling, and clustering these short lived, reactive species. Of particular note for cluster studies of radicals are those involving OH-Ne, N 2 , H 2 , 9 NH, CH-rare gases, 10 CN-Ne, 11 C 2 H 3 O-Ar, 12 C 5 H 5 -He, Ne, N 2 , 13 C 5 H 4 CH 3 -He, Ne, 13 and CH 3 O, 14 NCO, 15 and C 6 H 5 CH 2 /Ar, N 2 , CH 4 , C 2 H 6 , and C 3 H 8 . 16 Reports involving vdW clusters of aromatic radicals are limited to the benzyl, cyclopentadienyl, and methylcyclopentadienyl radicals to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…To model the excited state behavior of Xcpd-nonpolar solvent clusters we employ the Xcpd-Ar cluster data to fit C, H, X parameters under a number of simplifying assumptions. 8,9,12 These parameters are in turn employed to understand the other cluster spectra; in general, this program is reasonably successful.…”
Section: Introductionmentioning
confidence: 99%
“…Success in obtaining and interpreting spectra, and analyzing van der Waals ͑vdW͒ interactions and modes for open shell reactive intermediates in clusters has been achieved in only a limited number of instances. These solvation studies include OH, 2 NH, 3 CH, 4 CN, 5 HCO, 6 C 2 H 3 O, 7 CH 3 O, 8 NCO, 9 C 6 H 5 CH 2 , 10 C 5 H 5 , 11 C 5 H 4 CH 3 , 11 and a few others. Such radical solvation studies in the past have been mostly limited to nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%